Stateczność Płaskiej Postaci Zginania Dźwigarów Siatkowych o Pasach Równoległych - Misiak, J. (Engineering Transactions, 1973)
The aim of the paper is to solve the problem of stability of the plane form of bending of lattice girders with parallel flanges. On basis of the paper by H. FRACKIEWICZ "Buckling of lattice plates", the method applied is that of calculation of buckling of plane lattices by means of the theory of discrete media. The equations of equilibrium of the buckled girder are expressed in terms of dis- placements, and they yield the critical values of external loads as well as the corresponding form of buckling.